1972
DOI: 10.1002/app.1972.070160305
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to coagulation phenomena in wet‐spinning

Abstract: A. RENDE, S.T.I.R., Studio Tecnico Industriale, 80055 Portici, I h l y synopsis A new physicochemical model was built to describe the phenomena occurring during webspinning of polyacrylonitrile, in order to relate the integral time of coagulation to the major variables of the spinning bath. According to this model, counterdiffusion of solvent and coagulant leads the system to overcome the thermodynamic equilibrium conditions, so that precipitation of polymer occurs, at a distance from the fiber axis vari-abIe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 5 publications
(1 reference statement)
1
12
0
Order By: Relevance
“…[1][2][3][4] The mathematical models used to explain the diffusion process in wet-spinning are mainly the Moving-Boundary Model and Constant-Flux Ratio Model proposed by Paul. 5,6 In addition, Rende, 7 Liu et al, 8,9 and Knaul and Creber 10 also established similar models to describe the counter-diffusion phenomenon in wet-spinning and obtained similar result. However, the coagulation process in wet-spinning is very complex and there are still many puzzles to be pendent.…”
Section: Introductionsupporting
confidence: 72%
“…[1][2][3][4] The mathematical models used to explain the diffusion process in wet-spinning are mainly the Moving-Boundary Model and Constant-Flux Ratio Model proposed by Paul. 5,6 In addition, Rende, 7 Liu et al, 8,9 and Knaul and Creber 10 also established similar models to describe the counter-diffusion phenomenon in wet-spinning and obtained similar result. However, the coagulation process in wet-spinning is very complex and there are still many puzzles to be pendent.…”
Section: Introductionsupporting
confidence: 72%
“…3 Because of the dependence of subsequent textile properties of the fiber on its structure, particularly on the regularity of the cross-sectional shape, the integrity of the external skin, and the number and size of voids, accurate knowledge of the phenomena regulating these features is of great importance. 4 To our knowledge, earlier studies were just empirical attempts to correlate the actual spinning variables with the final properties of the fibers, 5,6 without any investigation on the dynamics of the phenomenon, and there is almost no reports on diffusion coefficient of solvent in polyacrylonitrile fiber formation process. In this study, H 2 O/ dimethyl sulfoxide (DMSO) mixture was used as the coagulation bath, acrylonitrile (AN)/ammonium itaconate (AIA) copolymers were used to prepare the spinning dopes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using modeling techniques to understand diffusion processes have been reported by Paul [4] and Rende and colleagues. [9] The determination of diffusion coefficients of H 2 O and dimethyl sulphoxide (DMSO) has been reported. [12−14] However, there are still some deficiencies.…”
Section: Introductionmentioning
confidence: 99%